Plasma cell balanitis (Zoon`s balanitis): A clinicopathological study of 8 cases - P. V. Krishna Rao; Hari Kishan Kumar Yadalla (Our Dermatology Online, 2012)
A disorder first described by Zoon in 1952, Zoon`s balanitis or Plasma cell balanitis (PCB), is an uncommon clinical disorder seen in middle-aged uncircumcised men. It is characterized by one or more indolent well demarcated, glazed, reddish brown patches on the glans penis or prepuce. The etiology of this disease is unknown. This balanitis does not respond to routine topical antifungals, steroid creams and systemic antifungals. Diagnosis is confirmed by biopsy. Herein we report 8 cases of PCB, presenting with a characteristic clinical picture of the disease. In all cases circumcision was done and histopathology confirmed the diagnosis of PCB. All patients were followed up for a period of 6 months and no recurrences were observed. Development of malignancy is not seen. In conclusion. We believe that for all cases of balanitis, not responding to routine topical antifungals, steroid creams and systemic antifungals, the diagnosis of Zoon`s balanitis should be considered.